WAKAF PRODUKTIF DALAM HUKUM ISLAM - Fatimah, Siti (USRATUNA: Jurnal Hukum Keluarga Islam, 2022)
This study explores the development of waqf from time to time, both from the history of Islam and the history of waqf in Indonesia, the research method used is qualitative literature. Productive waqf in addition to having a worship function also has a social function. social welfare (hablu minannas) to improve the welfare of Muslims, according to Law No. 41 of 2004 concerning waqf and its implementation, the management of nazir waqf must be more professional in its management to achieve the purpose, function, and designation of the waqf. Productive waqf in its development has been following Islamic law waqf in the era now refers to the welfare of the people, in its development and management. Productive waqf has a socio-religious dimension and the welfare of the people.